Trigonometric problem of moments with a port, the Levinson algorithms and certain applied problems - Ugrinovsky , R. A. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Eficient criteria for solvability of the trigonometric moment problem with a hatch in terms of coefficients of a recurrence relation governed by orthogonal polynomials on the unit circle are given. The criteria are based on the Levinson procedure. The potential, for applications is discussed.